Removal of Organic Dyes by Nanostructure ZnO-Bamboo Charcoal Composites with Photocatalysis Function. (9th June 2015) - Yu, Xinliang; Qin, Aimiao; Liao, Lei; Du, Rui; Tian, Ning; Huang, Song; Wei, Chun
Abstract : Composites of nanostructure zinc oxide (nano-ZnO) and bamboo charcoal (BC) were successfully prepared via impregnation-precipitation method. The products were characterized by XRD, SEM, and EDS. Rhodamine B (RhB) and acid fuchsin (AF) were selected as the organic dyes of photocatalysis degradation under the irradiation of ultraviolet light (UV). The influence of particle size of BC, irradiation time, pH value of the solution, and additive amount of H2 O2 on removal of the dyes has been studied. The results show that smaller particle size of BC in the composites has a better removal effect. The composites possess the highest removal capacity for RhB and AF under the conditions of pH = 2 and pH = 5.4, respectively. The optimum additive amount of H2 O2 for 5 mL RhB and AF was 0.050 mL and 0.1 mL, with a removal rate of 93% and 99%, respectively.